1994
DOI: 10.1016/0020-7292(94)90090-6
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV DNA in cervical and vaginal secretions: Prevalence and correlates among women in Nairobi, Kenya

Abstract: Objective.\p=m-\Factors that influence heterosexual transmission of the human immunodeficiency virus (HIV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
21
1
Order By: Relevance
“…In a cross-sectional study on 97 HIVpositive women, Clemetson et al 18 found a higher frequency of HIV isolation from the cervix and vagina in the women with ectopy. This association remained in the multivariate analysis: OR = 5; 95% CI = 1.5-16.9; p = 0.006.…”
Section: Hivmentioning
confidence: 98%
“…In a cross-sectional study on 97 HIVpositive women, Clemetson et al 18 found a higher frequency of HIV isolation from the cervix and vagina in the women with ectopy. This association remained in the multivariate analysis: OR = 5; 95% CI = 1.5-16.9; p = 0.006.…”
Section: Hivmentioning
confidence: 98%
“…The phenotype of genital HIV strains is primarily macrophage-tropic and non-syncytium-inducing (13). We elected to use MDM as target cells for HIV infection and as migrating cells, since genital tract tissues from HIV-infected individuals contain high levels of HIV-infected monocytes (12,25,46). Spira et al demonstrated that the first target cells for infection, observed within 2 days of intravaginal inoculation of simian immunodeficiency virus in macaques, are mononuclear cells in the lamina propria of the cervicovaginal mucosa (41).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, culture of GBS and polymerase chain reaction (PCR) tests for the detection of Chlamydia trachomatis in the genital secretions are widely used as maternal screening tools to prevent intrapartum mother-to-infant transmission of these pathogens. In previous studies, it was reported that the presence of viral DNA, including hepatitis B virus, human immunodeficiency virus (HIV), and HPV, in the maternal uterine cervical secretion or vaginal secretion may be a risk factor for mother-to-child transmission of viruses [1][2][3]. However, there have been no studies that evaluate the usability of PCR tests for CMV-DNA in the uterine cervical secretion as a tool for predicting congenital CMV infection before birth.…”
Section: Introductionmentioning
confidence: 99%